(untitled) (e-Journal of Linguistics, 2023)
In today’s society, travel is inevitable. With international visitor arrivals reaching 1,4 billion in 2018, almost one-fifth of the world’s population travels abroad. Travelers must have access to accurate information about their destination. Signage posted in several locations to replace the information desk workers must be tailored to minimize misleading misinformation. This page examines religious signs or signage in Denpasar, the capital of the globally renowned province of Bali, Indonesia. In this article, questions are raised regarding the equality of religious text meanings in the Indonesian-English translations of Denpasar’s signage. Photographs of nameboards and information were taken in four sub-districts to collect data, which was then examined from the standpoint of linguistic landscapes and translation science. The information is shown as text or outdoor signs. The study of the data indicates that the equivalent translation of the bilingual versions of the text is acceptable, with the exception of the linguistic structure. On the other hand, textual material can be regarded culturally, functionally, and descriptively acceptable, but the language of the content on present websites requires refinement.